Coaches Can Pray on Their Own Privately — But Cannot Lead Student-Athletes in Prayer: Joseph A. Kennedy v. Bremerton School District 597., U.S. ___; 2022 WL 2295034; 2022 U.S. Lexis 3218. Issue 1 (2nd January 2023) - Sawyer, Tonya L.
Abstract: This case involved a high school football coach in Bremerton, Washington. The defendant at the end of each game would privately pray at the middle of the football field. The practice was soon joined voluntarily by the players and others. The school board's attorney became concerned the practice would be seen as infringing on the Establishment Clause of the First Amendment separating church and state. The board attempted to negotiate with the Defendant to pray elsewhere or at a later time, but Defendant continued the practice. His contract was not renewed, leading the Defendant to sue the board and lost then appealed to the Ninth Circuit which ruled in favor of the school board and their argument regarding the Establishment Clause.